Benefit of measuring vedolizumab concentrations in inflammatory bowel disease patients in a real-world setting. (3rd August 2021) - Kolehmainen, Sara; Ylisaukko-oja, Tero; Jokelainen, Jari; Koivusalo, Mirkka; Jokiranta, T. Sakari; Sipponen, Taina
Abstract: Objectives: We set out to determine the reasons for serum vedolizumab (VDZ) trough concentration (TC) measurements in inflammatory bowel disease (IBD) patients and to evaluate treatment modifications after therapeutic drug measurement (TDM). We also evaluated the effect of increased dosing on patients' response to VDZ therapy. Methods: We performed a retrospective cohort study of IBD patients who received VDZ therapy at Helsinki University Hospital and whose VDZ levels were measured between June 2014 and December 2018. Results: Altogether, 90 patients (32 Crohn's disease and 58 ulcerative colitis) and 141 VDZ TC measurements were included. 24.1% of measurements took place during induction and 75.9% during the maintenance phase. During induction, 64.7% reached the target TC >20µg/ml. During maintenance therapy, 82.2% of VDZ TCs were within or exceeded the suggested target range of 5–15µg/ml. Reasons for TDM were: secondary nonresponse (44.0%), assessment of adequate VDZ TC (25.5%), primary nonresponse (12.8%), adverse events (6.4%), and other (11.3%). No treatment changes occurred after 60.3% of VDZ measurements. Increased dose frequency was used after 25.5% of VDZ measurements and 33.3% of these patients experienced improvement. Altogether, 31 (34.4%) patients discontinued the therapy due to inadequate treatment response. No anti-vedolizumab antibodies were detected. Conclusions: During the maintenance of VDZ therapy, the majority of VDZ TCs were within the suggested range. Measurement of VDZ TC did not lead to any treatment changes in two-thirds of patients. Dose optimization occurred in a quarter of patients and a third of them benefited from it.